PILOT PLANT FOR PRODUCTION OF FISH ENSILAGE AND THE ECONOMICS Of PRODUCTION - CHAKRABORTY, P K; JAMES, M ARUL (Fishery Technology, 2017)
This communication describes the design aspect and functions of individual pieces of equipment of a pilot plant for the production of fish ensilage based on lactic acid fermentation process. Details about the equipment, process flow sheet and equipment layout of the pilot plant have been given. An attempt has been made to prepare an estimate of the cost of production of liquid ensilage and solid feed mix.